Anti-corrosion anti-reflection composition as well as preparation method and application thereof

By combining bisphenol F epoxy acrylic resin with hollow silica microspheres and using ultraviolet curing and crosslinking agents, the problem of existing coatings being prepared at high temperatures and lack of corrosion resistance is achieved, and high efficiency is achieved , corrosion-resistant anti-reflective coating prepared at low temperature improves light transmittance and coating performance.

CN119463646APending Publication Date: 2025-02-18SUZHOU LINGHUI MATERIAL TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411142631.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-20
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing anti-reflective coatings require high temperatures during film making and lack corrosion resistance, making them difficult to be effectively used in harsh external environments.

Method used

Bisphenol F epoxy acrylic resin and hollow silica microspheres are combined to reduce the reaction temperature by ultraviolet light curing, and a crosslinking agent and photoinitiator are added to improve the corrosion resistance and wear resistance of the coating.

Benefits of technology

The coating is prepared at lower temperatures, improving its corrosion resistance and anti-reflection properties, enhancing light transmittance and maintaining the transparency of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463646A_ABST
    Figure CN119463646A_ABST
Patent Text Reader

Abstract

The invention discloses an anti-corrosion anti-reflection composition which mainly comprises bisphenol F epoxy acrylic resin and silicon dioxide microspheres, and the mass ratio of the bisphenol F epoxy acrylic resin to the silicon dioxide microspheres is 1: (0.8-1.21). The preparation method comprises the following steps: synthesizing the bisphenol F epoxy acrylic resin, adding the silicon dioxide microspheres, the cross-linking agent and the photoinitiator into the resin, and the like. The invention also discloses application of the composition as a coating on a display and a solar panel. The application method comprises the following steps: coating a substrate with the composition, removing the solvent, and curing with an ultraviolet lamp. The coating prepared from the composition can improve the light transmittance and the corrosion resistance at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of optical films, and in particular to an anti-corrosion and anti-reflection film composition. Background Art

[0002] In recent years, due to the improvement of solar panels' efficiency in absorbing sunlight and the need for display panels to reduce reflected light sources, the demand for anti-reflective coatings has been increasing. In addition, since solar panels are deployed in relatively harsh external environments, there is also a certain demand for corrosion resistance, so it is particularly important to produce a coating that has both corrosion resistance and reduces light reflection.

[0003] At present, most anti-reflection coatings are formed by hydrolyzing low-refractive index materials such as SiO2, ZnO, MgF2 and TiO2. Not only does the reaction time take a long time, but the film-making process often requires high temperatures, and the film-making substrate has high heat resistance requirements. For example, patents CN 118185351 "An anti-reflection coating, preparation method and application thereof" and CN 117924979A "A linear high polysilane enhanced wear-resistant anti-reflection coating and preparation method thereof" use SiO2 sol coatings, and patent CN103153862 A "Preparation method of hollow magnesium fluoride particles and anti-reflection coating, optical device and imaging optical system with the particles" uses MgF2 sol. Although hollow silica particles are used in Japanese patent JP 6103950 B2 "Method for manufacturing hollow particles, method for manufacturing anti-reflection film and method for manufacturing optical element", there is little or no mention of corrosion resistance testing in the above patents. Therefore, how to lower the reaction temperature during the film-making process while still having a certain degree of corrosion resistance has become a technical difficulty in this field. Summary of the invention

[0004] Purpose of the invention: The present invention provides an anti-corrosion and anti-reflection composition, which can be used as a coating and applied to a display or a solar panel, thereby solving the problem that the coating in the prior art does not have anti-corrosion ability.

[0005] Technical solution: The anti-corrosion anti-reflection composition of the present invention mainly comprises bisphenol F epoxy acrylic resin and silica microspheres, wherein the bisphenol F epoxy acrylic resin is obtained by grafting bisphenol F epoxy resin with acrylic acid, and the mass ratio of the bisphenol F epoxy acrylic resin to the silica microspheres is 1:0.8-1.2, preferably 1:1.

[0006] Bisphenol F epoxy acrylic resin has excellent acid, alkali and solvent resistance, which helps to improve the corrosion resistance of the composition, and can be cured by ultraviolet light, which greatly reduces the reaction temperature when the composition is used to prepare a coating.

[0007] The particle size of the silica microspheres is 40-60 nm, preferably 40-50 nm, and the silica microspheres are hollow.

[0008] Hollow silica microspheres greatly enhance the anti-reflection ability of the coating. If the particle size of the hollow silica microspheres is less than 40nm, the hollow silica microspheres are too small, the hollow area is too low, and the refractive index increases, resulting in a decrease in the anti-reflection effect. If the particle size of the hollow silica microspheres is greater than 60nm, the unit area of ​​the hollow silica microspheres in the coating increases, reducing the mechanical properties of the coating. Considering the refractive index and mechanical properties of the coating, the particle size of the hollow silica microspheres is selected to be 40-60nm.

[0009] The anti-corrosion anti-reflection composition also includes a crosslinking agent; the crosslinking agent is ethylene glycol dimethacrylate and / or tripropylene glycol diacrylate; the mass ratio of ethylene glycol dimethacrylate, tripropylene glycol diacrylate to bisphenol F epoxy acrylic resin is 0.08-0.12:1 respectively; the preferred mass ratio is 0.1:1.

[0010] The crosslinking agents ethylene glycol dimethacrylate and tripropylene glycol diacrylate are added to improve the wear resistance and hardness of the composition when used as a coating.

[0011] The anti-corrosion anti-reflection composition also includes a solvent for dilution when used as a coating; the preferred solvent is ethyl acetate or butanone; the mass ratio of the solvent to the bisphenol F epoxy acrylic resin is 1:20-30; the preferred mass ratio is 1:25.

[0012] The anti-corrosion and anti-reflection composition also includes a photoinitiator; the photoinitiator is 1-hydroxycyclohexyl phenyl ketone or 2-methyl-1-(4-methylthiophenyl)-2-morpholine-1-propanone; the mass ratio of the photoinitiator to the bisphenol F epoxy acrylic resin is: 0.03-0.035; the preferred mass ratio is 1:0.033.

[0013] The method for preparing the above-mentioned anti-corrosion anti-reflection composition comprises the steps of:

[0014] (1) obtaining bisphenol F epoxy acrylic resin by grafting acrylic acid onto bisphenol F epoxy resin;

[0015] (2) Adding silica microspheres, a crosslinking agent, and a photoinitiator to the obtained bisphenol F epoxy acrylic resin, and adding a solvent to dilute and mix well to obtain the composition.

[0016] Wherein, the mass ratio of the bisphenol F epoxy acrylic resin to the silica microspheres is 1:0.8-1.2, preferably 1:1.

[0017] The particle size of the silica microspheres is 40-60 nm, preferably 40-50 nm, and the silica microspheres are hollow.

[0018] The crosslinking agent is ethylene glycol dimethacrylate and / or tripropylene glycol diacrylate; the mass ratio of ethylene glycol dimethacrylate and tripropylene glycol diacrylate to bisphenol F epoxy acrylic resin is 0.08-0.12:1 respectively; the preferred mass ratio is 0.1:1.

[0019] The solvent used for dilution is ethyl acetate or butanone; the mass ratio of the solvent to the bisphenol F epoxy acrylic resin is 1:20-30; the preferred mass ratio is 1:25.

[0020] The anti-corrosion and anti-reflection composition also includes a photoinitiator; the photoinitiator is 1-hydroxycyclohexyl phenyl ketone or 2-methyl-1-(4-methylthiophenyl)-2-morpholine-1-propanone; the mass ratio of the photoinitiator to the bisphenol F epoxy acrylic resin is: 0.03-0.035; the preferred mass ratio is 1:0.033.

[0021] In step (1), the preparation of the bisphenol F epoxy acrylic resin comprises the steps of:

[0022] (a) mixing bisphenol F epoxy resin and acrylic acid, and adding a polymerization inhibitor in batches at a temperature of 40-60° C. to obtain an intermediate;

[0023] (b) reacting the intermediate at a temperature of 90-110° C. to obtain a bisphenol F epoxy acrylic resin;

[0024] And / or, the polymerization inhibitor is tetramethylammonium chloride and / or hydroquinone.

[0025] Wherein, the mass ratio of the bisphenol F epoxy resin, tetramethylammonium chloride acrylate and hydroquinone is 1:0.75-0.85:0.008-0.012:0.0008-0.0012; the preferred mass ratio is 1:0.8:0.01:0.001.

[0026] In step (a), the polymerization inhibitor is added in batches within 1 hour at a temperature of 50° C., preferably in a dropwise manner.

[0027] The application of the above-mentioned anti-corrosion anti-reflection composition as a coating on a display and / or a solar panel,

[0028] The method for applying the anti-corrosion anti-reflection composition of the present invention as a coating comprises the steps of coating the composition on a substrate, removing the solvent, and curing with an ultraviolet lamp.

[0029] And / or, the solvent is removed by heating; preferably, the temperature for removing the solvent is 80-120°C; further preferably, the temperature is 80°C.

[0030] Preferably, the energy of the UV lamp curing is 300-500 mJ / m 3 Further preferably, the energy of UV curing is 300-400mJ / m 3 .

[0031] After coating, the solvent is dried in an oven and cured under UV light without high temperature treatment.

[0032] Preferably, the coating thickness is 100-200 nm. The thinner the coating, the worse the mechanical properties of the coating. The thicker the coating, the worse the optical properties.

[0033] Beneficial effects: The composition of the present invention mainly comprises bisphenol F epoxy acrylic resin which is corrosion-resistant and can be cured by ultraviolet light, hollow silica microspheres which improve anti-reflection ability, ethylene glycol dimethacrylate and tripropylene glycol diacrylate which improve wear resistance and hardness. The composition is diluted with a solvent and then coated on a substrate as a coating, so that the substrate transmittance is increased from the original 88.4% to 92.6%, which greatly improves the light transmittance. In addition, in the tests of solvent resistance and acid and alkali resistance, the light transmittance of the coating is still maintained. The coating prepared using the composition of the present invention can simultaneously improve the light transmittance and corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 It is a comparison chart of the transmittance of the PET substrate before and after the anti-reflection coating of the present invention is coated;

[0035] Figure 2 This is a comparison chart of the transmittance of PET coated with an anti-reflection coating before and after the corrosion resistance test;

[0036] It should be noted that the attached Figure 1 and attached Figure 2 The text in this is for performance testing only. DETAILED DESCRIPTION

[0037] The present invention is described in detail below through a plurality of embodiments and comparative examples.

[0038] Example 1

[0039] The preparation process of the anti-corrosion anti-reflection composition is as follows:

[0040] S1. Preparation of bisphenol F epoxy acrylic resin: bisphenol F epoxy resin, acrylic acid, tetramethylammonium chloride and hydroquinone were added into a three-necked flask and a constant pressure bottom liquid funnel in a mass ratio of 1:0.8:0.01:0.001 according to the reaction requirements, respectively, heated to 100° C., and reacted for 4 hours to obtain bisphenol F epoxy acrylic resin.

[0041] S2. Mix bisphenol F epoxy acrylate, 40 nm hollow silica, ethylene glycol dimethacrylate, tripropylene glycol diacrylate, 1-hydroxycyclohexyl phenyl ketone, ethyl acetate or butanone in a mass ratio of 1:1.1:0.1:0.1:0.033:25, and stir on a three-roll mill for 1 hour at room temperature to finally obtain an anti-corrosion anti-reflection composition, which can also be used as a coating liquid for a coating.

[0042] The coating solution prepared by S2 was applied on the PET substrate. The coating thickness was controlled to be 100 nm according to the number of the wire rod. After coating, the substrate was placed in an oven at 80 °C to remove the solvent. Then, the substrate was heated at 300 mJ / cm 3 The PET film is cured under ultraviolet light to obtain a PET film coated with an anti-corrosion and anti-reflection coating.

[0043] Characteristic tests were performed on the prepared coatings:

[0044] By testing the optical transmittance of the PET substrate, it can be found that the optical transmittance of the original PET film without the above coating is 88.4%, and the optical transmittance of the original PET film with the above coating is 92.6%, an increase of 4.2%. In addition, the hardness of the original PET film has also been increased from HB to 2HB. According to the national standard "Determination of Liquid Resistance of Paints and Varnishes", the coating was tested for resistance to 0.1mol / L hydrochloric acid, 0.1mol / L sodium hydroxide, ethanol, and ethyl acetate solutions. The results showed that the transmittance of the coating was maintained within 15 days.

[0045] Example 2

[0046] The preparation process of the anti-corrosion anti-reflection composition is as follows:

[0047] S1. Preparation of bisphenol F epoxy acrylic resin: bisphenol F epoxy resin, acrylic acid, tetramethylammonium chloride and hydroquinone were added into a three-necked flask and a constant pressure bottom liquid funnel in a mass ratio of 1:0.8:0.01:0.001 according to the reaction requirements, respectively, heated to 100° C., and reacted for 4 hours to obtain bisphenol F epoxy acrylic resin.

[0048] S2. Mix bisphenol F epoxy acrylate, 50 nm hollow silica, ethylene glycol dimethacrylate, tripropylene glycol diacrylate, 1-hydroxycyclohexyl phenyl ketone, and ethyl acetate in a mass ratio of 1:1.1:0.1:0.1:0.033:25, and stir on a three-roll mill for 1 hour at room temperature to finally obtain an anti-corrosion anti-reflection composition, which can also be used as a coating liquid for a coating.

[0049] The coating liquid prepared by S2 was applied on the PET substrate. The coating thickness was controlled to be 100 nm according to the number of the wire rod. After the coating was completed, it was placed in an oven at 80°C to remove the solvent, and then cured under a UV lamp at 300mJ / cm3 to finally obtain a PET film coated with an anti-corrosion and anti-reflection coating.

[0050] Characteristic tests were performed on the prepared coatings:

[0051] By testing the optical transmittance of the PET substrate, it can be found that the optical transmittance of the original PET film without the above coating is 88.4%, and the optical transmittance of the original PET film with the above coating is 92.4%, an increase of 4.0%. In addition, the hardness of the original PET film has also been increased from HB to 2HB. According to the national standard "Determination of Liquid Resistance of Paints and Varnishes", the coating was tested for resistance to 0.1mol / L hydrochloric acid, 0.1mol / L sodium hydroxide, ethanol, and ethyl acetate solutions. The results showed that the transmittance of the coating was maintained within 15 days.

[0052] Example 3

[0053] The preparation process of the anti-corrosion anti-reflection composition is as follows:

[0054] S1. Preparation of bisphenol F epoxy acrylic resin: bisphenol F epoxy resin, acrylic acid, tetramethylammonium chloride and hydroquinone were added into a three-necked flask and a constant pressure bottom liquid funnel in a mass ratio of 1:0.8:0.01:0.001 according to the reaction requirements, respectively, heated to 100° C., and reacted for 4 hours to obtain bisphenol F epoxy acrylic resin.

[0055] S2. Prepare an anti-reflection coating liquid: mix bisphenol F epoxy acrylate, 40 nm hollow silica, ethylene glycol dimethacrylate, tripropylene glycol diacrylate, 1-hydroxycyclohexyl phenyl ketone, and ethyl acetate in a mass ratio of 1:1.1:0.1:0.1:0.033:25, and stir on a three-roll mill for 1 hour at room temperature to finally obtain an anti-corrosion anti-reflection composition, which can also be used as a coating liquid for a coating.

[0056] The coating liquid prepared by S2 was applied on the PET substrate. The coating thickness was controlled to be 200 nm according to the number of the wire rod. After coating, the substrate was placed in an oven at 80 °C to remove the solvent. Then, the substrate was heated at 300 mJ / cm3 The PET film is cured under ultraviolet light to obtain a PET film coated with an anti-corrosion and anti-reflection coating.

[0057] Characteristic tests were performed on the prepared coatings:

[0058] By testing the optical transmittance of the PET substrate, it can be found that the optical transmittance of the original PET film without the above coating is 88.4%, and the optical transmittance of the original PET film with the above coating is 92.3%, an increase of 3.9%. According to the national standard "Determination of Liquid Resistance of Paints and Varnishes", the coating was tested for resistance to 0.1mol / L hydrochloric acid, 0.1mol / L sodium hydroxide, ethanol, and ethyl acetate solutions. The results showed that the transmittance of the coating was maintained within 15 days.

[0059] Example 4

[0060] The preparation process of the anti-corrosion anti-reflection composition is as follows:

[0061] S1. Preparation of bisphenol F epoxy acrylic resin: bisphenol F epoxy resin, acrylic acid, tetramethylammonium chloride and hydroquinone were added into a three-necked flask and a constant pressure bottom liquid funnel in a mass ratio of 1:0.8:0.01:0.001 according to the reaction requirements, respectively, heated to 100° C., and reacted for 4 hours to obtain bisphenol F epoxy acrylic resin.

[0062] S2. Prepare an anti-reflection coating liquid: mix bisphenol F epoxy acrylate, 40 nm hollow silica, ethylene glycol dimethacrylate, tripropylene glycol diacrylate, 1-hydroxycyclohexyl phenyl ketone, and ethyl acetate in a mass ratio of 1:1.1:0.1:0.1:0.033:25, and stir on a three-roll mill for 1 hour at room temperature to finally obtain an anti-corrosion anti-reflection composition, which can also be used as a coating liquid for a coating.

[0063] The coating solution prepared by S2 was applied on the PET substrate. The coating thickness was controlled to be 100 nm according to the number of the wire rod. After coating, the substrate was placed in an oven at 80 °C to remove the solvent. Then, the substrate was heated at 400 mJ / cm 3 The PET film is cured under ultraviolet light to obtain a PET film coated with an anti-corrosion and anti-reflection coating.

[0064] Characteristic tests were performed on the prepared coatings:

[0065] By testing the optical transmittance of the PET substrate, it can be found that the optical transmittance of the original PET film without the above coating is 88.4%, and the optical transmittance of the original PET film with the above coating is 92.5%, an increase of 4.1%. In addition, the hardness of the original PET film has also increased from HB to 2HB. According to the national standard "Determination of Liquid Resistance of Paints and Varnishes", the coating was tested for resistance to 0.1mol / L hydrochloric acid, 0.1mol / L sodium hydroxide, ethanol, and ethyl acetate solutions. The results showed that the transmittance of the coating was maintained within 15 days.

[0066] Example 5

[0067] The preparation process of the anti-corrosion anti-reflection composition is as follows:

[0068] S1. Preparation of bisphenol F epoxy acrylic resin: bisphenol F epoxy resin, acrylic acid, tetramethylammonium chloride and hydroquinone were added into a three-necked flask and a constant pressure bottom liquid funnel in a mass ratio of 1:0.8:0.01:0.001 according to the reaction requirements, respectively, heated to 100° C., and reacted for 4 hours to obtain bisphenol F epoxy acrylic resin.

[0069] S2. Mix bisphenol F epoxy acrylate, 40 nm hollow silica, ethylene glycol dimethacrylate, tripropylene glycol diacrylate, 2-methyl-1-(4-methylthiophenyl)-2-morpholine-1-propanone, and ethyl acetate in a mass ratio of 1:1.1:0.1:0.1:0.033:25, and stir on a three-roll mill for 1 hour at room temperature to finally obtain an anti-corrosion anti-reflection composition, which can also be used as a coating liquid for a coating.

[0070] The coating solution prepared by S2 was applied on the PET substrate. The coating thickness was controlled to be 100 nm according to the number of the wire rod. After coating, the substrate was placed in an oven at 80 °C to remove the solvent. Then, the substrate was heated at 300 mJ / cm 3 The PET film is cured under ultraviolet light to obtain a PET film coated with an anti-corrosion and anti-reflection coating.

[0071] Characteristic tests were performed on the prepared coatings:

[0072] By testing the optical transmittance of PET substrate, such as Figure 1 As shown, it can be found that the optical transmittance of the original PET film without the above coating is 88.4%, and the optical transmittance of the original PET film with the above coating is 92.3%, an increase of 3.9%. And the hardness of the original PET film is also increased from HB to 2HB. According to the national standard "Determination of Liquid Resistance of Paints and Varnishes", the coating was tested for resistance to 0.1mol / L hydrochloric acid, 0.1mol / L sodium hydroxide, ethanol, and ethyl acetate solutions. Figure 2 As shown, the results indicate that the coating transmittance is maintained over fifteen days.

[0073] Comparative Example 1

[0074] The bisphenol A epoxy acrylic resin on the market was selected to replace the bisphenol F epoxy acrylic resin in Scheme 1, and other conditions remained unchanged. The results showed that the optical transmittance of the coating reached 92.5%, but in the 0.1 mol / L sodium hydroxide solution resistance test, after three days, the optical transmittance of the coating dropped to the same level as the transmittance of the original PET film.

[0075] Comparative Example 2

[0076] When the coating thickness in Scheme 1 was increased to 300 nm and other conditions remained unchanged, the results showed that the optical transmittance of the coating decreased to 91.4%, indicating that the increase in coating thickness would lead to a decrease in the optical performance of the coating.

[0077] Comparative Example 3

[0078] The 40nm hollow silica microspheres in Scheme 1 were changed to 80nm hollow silica microspheres, and other conditions remained unchanged. The results showed that the optical transmittance of the coating was reduced to 90.4%, indicating that the increase in the particle size of the hollow silica microspheres would lead to a decrease in the optical performance of the coating.

[0079] Comparative Example 4

[0080] When ethylene glycol dimethacrylate and tripropylene glycol diacrylate in Scheme 1 were not added to the coating solution and other conditions remained unchanged, the results showed that the hardness of the coating dropped to HB, indicating that the addition of ethylene glycol dimethacrylate and tripropylene glycol diacrylate helped to improve the hardness of the coating.

Claims

1. An anti-corrosion anti-reflection composition, characterized in that: The invention mainly comprises bisphenol F epoxy acrylic resin and silicon dioxide microspheres, wherein the bisphenol F epoxy acrylic resin is obtained by grafting bisphenol F epoxy resin with acrylic acid, and the mass ratio of the bisphenol F epoxy acrylic resin to the silicon dioxide microspheres is 1:0.8-1.

3.

2. The anti-corrosion anti-reflection composition according to claim 1, characterized in that: The particle size of the silica microspheres is 40-60 nm; And / or, the silica microspheres are hollow and have a particle size of 40-50 nm.

3. The anti-corrosion anti-reflection composition according to claim 1, characterized in that: Also included are cross-linking agents; And / or, the cross-linking agent is ethylene glycol dimethacrylate and / or tripropylene glycol diacrylate; Preferably, the mass ratio of ethylene glycol dimethacrylate, tripropylene glycol diacrylate and bisphenol F epoxy acrylic resin is 0.08-0.12:1 respectively; Further preferably, the mass ratio of the ethylene glycol dimethacrylate, tripropylene glycol diacrylate and bisphenol F epoxy acrylic resin is 0.1:1; And / or, the anti-corrosion anti-reflection composition further comprises a solvent for dilution; Preferably, the solvent is ethyl acetate or butanone; Further preferably, the mass ratio of the solvent to the bisphenol F epoxy acrylic resin is 1:20-30; More preferably, the mass ratio of the solvent to the bisphenol F epoxy acrylic resin is 1:

25.

4. The anti-corrosion anti-reflection composition according to claim 1, characterized in that: Also included are photoinitiators; and / or, the photoinitiator is 1-hydroxycyclohexyl phenyl ketone or 2-methyl-1-(4-methylthiophenyl)-2-morpholine-1-propanone (907); Preferably, the mass ratio of the photoinitiator to the bisphenol F epoxy acrylic resin is 1:0.03-0.035; Further preferably, the mass ratio of the 1-hydroxycyclohexyl phenyl ketone to the bisphenol F epoxy acrylic resin is 1:0.

033.

5. A method for preparing an anti-corrosion anti-reflection composition, characterized in that: Includes steps: (1) obtaining bisphenol F epoxy acrylic resin by grafting acrylic acid onto bisphenol F epoxy resin; (2) Adding silica microspheres, a crosslinking agent, and a photoinitiator to the obtained bisphenol F epoxy acrylic resin, and adding a solvent to dilute and mix well to obtain the composition.

6. The preparation method according to claim 5, characterized in that: The preparation of the bisphenol F epoxy acrylic resin comprises the following steps: (a) mixing bisphenol F epoxy resin and acrylic acid, and adding a polymerization inhibitor in batches at a temperature of 40-60° C. to obtain an intermediate; (b) reacting the intermediate at a temperature of 90-110° C. to obtain a bisphenol F epoxy acrylic resin; And / or, the polymerization inhibitor is tetramethylammonium chloride and / or hydroquinone.

7. The preparation method according to claim 6, characterized in that: The mass ratio of the bisphenol F epoxy resin, tetramethylammonium chloride acrylate and hydroquinone is 1:0.75-0.85:0.008-0.012:0.0008-0.0012; Preferably, the mass ratio of the bisphenol F epoxy resin, tetramethylammonium chloride acrylate and hydroquinone is 1:0.8:0.01:0.

001.

8. The preparation method according to claim 6, characterized in that: In step (a), the inhibitor is added in batches within 1 hour at a temperature of 50°C.

9. An application of an anti-corrosion anti-reflection composition, characterized in that: The composition is used as a coating on displays and / or solar panels.

10. An application method of an anti-corrosion anti-reflection composition, characterized in that: The method comprises the steps of coating the composition on a substrate, removing the solvent, and curing with an ultraviolet lamp; And / or, the removal of the solvent is carried out by heating; Preferably, the temperature for removing the solvent is 80-120°C; Further preferably, the temperature for removing the solvent is 80°C; Preferably, the energy of the UV lamp curing is 300-500 mJ / m 3 ; Further preferably, the energy of the UV lamp curing is 300-400 mJ / m 3 ; Preferably, the coating thickness is 100-200 nm.

Citation Information

Patent Citations

  • Method of producing hollow magnesium fluoride particles, and antireflection coating, optical device, and imaging optical system having the particles

    CN103153862A

  • Linear high polysilane reinforced wear-resistant antireflection coating and preparation method thereof

    CN117924979A

  • Method for producing hollow particles, method for producing antireflection film, and method for producing optical element

    JP6103950B2

  • Antistatic, anti-dazzle and anti-reflection optical film and manufacture method for the same and application thereof

    CN107203013A

  • Flexible anti-static anti-reflection optical film, anti-static anti-reflection coating liquid and preparation method thereof

    CN113064226A